Study of Geotechnical Characteristics for The Deposits of The Samarra Dam Reservoir and The Upper Tigris Tharthar Arm Area and Their Engineering Suitability (Iraqi National Journal of Earth Science (INJES), 2026)
The research included finding the geotechnical properties of the Samarra Dam Reservoir sediments in three locations and the Tharthar Depression sediments in four locations. Physical tests showed that the moisture content of the sediments varies according to the flood and drought seasons. The moisture content was studied during August in the year 2023 and the month of January in the year 2024, and the results showed a clear difference. Between the months the moisture content (wc%) value in August was (11%_5%) and in January the moisture content (wc%) was (40%_26.2%).While it appears from the results of the specific gravity (G.S.) that it ranges (2.62_2.7), the results of the volumetric analysis showed that the predominant percentage of the deposits of the study area is sand, ranging from (40%_60%), which is mostly sand deposits mixed with silt, with varying percentages of clay.From the plasticity limits, the results showed the liquidity limit L.L (19.1%_24.79%), the plasticity limit P.L (11.22%_14.99%), and the plasticity coefficient P.I (5.83%_9.8%). The plasticity diagram revealed the quality of the ML-type sediments.The mechanical tests conducted for the sediments were direct shear tests where values were: Cohesion (C) (0_4) and internal friction angle values (Ø) (360_460), and from the standard compaction test (Proctor) it was revealed that the value of the optimum water content (OMC) (9%_17%) and the values of dry density (MDD)) (1.46_1.61). ). Chemical tests showed that the deposits are basic with low organic content and contain gypsum and chlorides at levels exceeding 1%, which leads to negative effects such as corrosion, cracking, and moderate effects from sulfates. However, caution is required regarding corrosion and cracking. The deposits also contain sulfates and soluble salts in moderate amounts, but attention should be paid to avoid corrosion and cracking. These deposits are of the type transported by water, which has led to changes in their engineering properties. Mineralogical study showed that the deposits in the study area, especially in the Samarra Dam reservoir, contain a high proportion of quartz and carbonate minerals and lack clay minerals. This is due to the fact that the predominant proportion of the deposits is sand, which gradually increases in clay minerals from the entrance of the Tharthar regulator to the end of the Tharthar Channel, but their proportion remains relatively small. but their percentage remains somewhat small. It cannot be used in construction industries such as brick and ceramic manufacturing, and the reason is that most of the sediments in the study area are sandy. It can be used in the manufacture of filters to purify the river stream of sewage waste, as well as in concrete mixes. It can also be used in the manufacture of sand bricks after treating them with certain proportions of limestone, and it is also used for agricultural purposes.
Keywords: Samarra, Al-Tharthar channel, Transported Sediments, Geotechnics